Everolimus immunosuppression in kidney transplantation: what is the optimal strategy? - Witzke, Oliver; Sommerer, Claudia; Arns, Wolfgang (Transplantation reviews, 2016)
Two main everolimus-based strategies have been pursued to facilitate calcineurin inhibitor (CNI) reduction after kidney transplantation: (i) everolimus with reduced CNI exposure from time of transplant and (ii) pre-emptive introduction of everolimus with CNI reduction or withdrawal at some point post-transplant. Randomized trials have shown no loss of immunosuppressive efficacy for everolimus (targeting 3-8ng/mL) with reduced-exposure CNI versus standard-exposure CNI and mycophenolic acid (MPA) in low-to-moderate risk patients. Renal function has tended to be numerically, but not significantly, higher with everolimus and reduced-CNI versus MPA and standard-CNI. One study which used very low CsA exposure in everolimus-treated patients reported a substantial improvement in estimated GFR compared to controls, but this requires confirmation. Pre-emptive conversion to everolimus at three to six months after kidney transplantation significantly improves long-term renal function, but with an increased rate of mild acute rejection. Earlier conversion (up to two months post-transplant) can lead to an increase in rejection risk, while later conversion (more than six months post-transplant) is unproductive unless baseline renal function is good. This article considers the risks and benefits associated with either strategy, and reviews specific clinical situations that influence the optimal approach in individual patients. The balance of evidence suggests two options. De novo everolimus with reduced CNI, steroids and induction therapy ensures immunosuppressive efficacy in low- or standard-risk populations, and investigations into this strategy are ongoing. Conversion to everolimus with CNI withdrawal between three and six months post-transplant offers a long-term renoprotective effect if baseline graft function is good.
Available online 18 September 2015
Gesehen am 03.07.2020